2015
DOI: 10.1159/000431104
|View full text |Cite
|
Sign up to set email alerts
|

da Vinci and Open Radical Prostatectomy: Comparison of Clinical Outcomes and Analysis of Insurance Costs

Abstract: Purpose: To assess clinical outcomes and reimbursement costs of open and robotic-assisted radical prostatectomies in Germany. Methods: Perioperative data of 499 open (2003-2006) and 932 (2008-2010) robotic-assisted radical prostatectomies as well as longitudinal reimbursement costs of an anonymized health insurance research database from Germany containing data of patients who underwent robotic-assisted or open radical prostatectomy were retrospectively analysed in a single-centre study. Results: Significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 29 publications
1
27
0
1
Order By: Relevance
“…In 1997, a cholecystectomy was the first robotic-assisted surgery performed in Belgium. Robotic-assisted surgery was shaped by the then only system available - the DaVinci® surgical system (Intuitive Surgical, Sunnyvale, CA, USA) [2]. Because of the high and unreimbursed costs and the comparably long process times, robotic-assisted operations have only become established in urological surgery.…”
Section: Introductionmentioning
confidence: 99%
“…In 1997, a cholecystectomy was the first robotic-assisted surgery performed in Belgium. Robotic-assisted surgery was shaped by the then only system available - the DaVinci® surgical system (Intuitive Surgical, Sunnyvale, CA, USA) [2]. Because of the high and unreimbursed costs and the comparably long process times, robotic-assisted operations have only become established in urological surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Applying a standardized reporting methodology, like the modified Clavien-Dindo classification (CDC) [1], it is found that the overall complication rate of the procedure can be as high as 42.5% [2] . Easily applicable objective models that evaluate the postoperative risk of morbidity and mortality of radical prostatectomy are rare.…”
Section: Introductionmentioning
confidence: 99%
“…Searching in the literature, the most recurrent issues concerning surgical robots and insurance are about the coverage of specific surgical interventions by the national health insurance service [39,40] and about the reduced health insurance costs resulting from robotic assisted surgery [41]. These issues are relevant also for other medical applications of robots, such as prosthetic devices, as reported by [2].…”
Section: Service Robotsmentioning
confidence: 99%